Soft tissue lasers: an innovative tool enhancing treatment outcomes in orthodontics – a narrative review - Ahmed, Aqeel; Fida, Mubassar; Javed, Faizan; Maaz, Muhammad; Shoukat Ali, Umair (Journal of the Pakistan Medical Association, 2022)
Lasers have been utiliSed in the field of dentistry for over 40 years, but their use has been limited in the field of orthodontics. The advent of lasers with accompanying computer interfaces has made them significantly user-friendly, adding to their appeal in the orthodontic profession. Knowledge regarding the laser device's capabilities and limitations is essential to optimise patient care and to make a satisfactory investment return. For the effective and successful integration of lasers in orthodontic practice, adequate training is required, limited not only to the orthodontist but the dental assistants and auxiliaries as well. Orthodontists may safely and readily execute gingivectomy, exposure of teeth, frenectomy, circumferential supracrestal fiberotomy, ankyloglossia release and uvulopalatoplasty. The current narrative review was planned to introduce the benefits and general principles of soft tissue lasers in the field of orthodontics and recent surgical research comparing different laser-assisted surgeries against conventional scalpel surgeries.